Summertime Moisture Sources and Transportation Pathways for China and Associated Atmospheric Circulation Patterns - Zhang, Ruonan; Chu, QuCheng; Zuo, Zhiyan; Qi, Yanjun (Frontiers in Earth Science, 2021)
Based on the Lagrangian particle dispersion model, HYSPLIT 4.9, this study analyzed the summertime atmospheric moisture sources and transportation pathways affecting six subregions across China. The sources were: Midlatitude Westerly (MLW), Siberian-Arctic regions (SibArc), Okhotsk Sea (OKS), Indian Ocean (IO), South China Sea (SCS), Pacific Ocean (PO), and China Mainland (CN). Furthermore, the relative contributions of these seven moisture sources to summertime precipitation in China were quantitatively assessed. Results showed that the CN precipitation source dominates the interannual and interdecadal variation of precipitation in most subregions, except Southwest and South China. The Northeast China vortex and Pacific–Japan (PJ) teleconnection, which transport water vapor from the MLW, OKS and PO sources, are crucial atmospheric systems and patterns for the variation of precipitation in Northeast China. The interannual variation of precipitation in Northwest and North China is mainly dominated by mid–high-latitude Eurasian wave trains, which provide the necessary dynamical conditions and associated moisture transport from the MLW and SibArc sources. In addition, an enhanced western North Pacific subtropical high (WNPSH) accompanied by the East Asian–western North Pacific summer monsoon and PJ teleconnection, transports extra moisture to North China from the SCS and PO sources, as well to the Yangtze River Valley and South China. The Indian summer monsoon (ISM) is also critically important for the interdecadal change in precipitation over the Yangtze River Valley and South China, via the southwesterly branch of moisture transport from the IO source. The interdecadal changes in precipitation over Southwest China are determined by the IO and SCS sources, via enhanced WNPSH coupling with a weakened ISM. These results suggest that the interdecadal and interannual variations of moisture sources contribute to the attendant variation of summertime precipitation in China via large-scale circulation regimes in both the mid–high and lower latitudes.